Model Struktur Organisasi Kolaboratif Pada Lembaga Dakwah Dan Pengaruhnya Terhadap Etos Kerja Karyawan - siti trizuwani; Suparto . (GLOBAL SCIENTS PUBLISHER, 2025)
The organizational structure of Islamic da’wah institutions in Indonesia is still dominated by hierarchical models that create barriers in coordination, communication, and employee participation. This study aims to conceptually analyze how the implementation of a collaborative organizational structure can strengthen employee work ethic within da’wah institutions. The method used is a literature review by examining national journals, organizational management books, and scientific publications related to da’wah and organizational structure from 2014–2024. The analysis was conducted through theme identification, concept categorization, and argumentative synthesis. The findings show that a collaborative organizational structure which includes decentralization, two-way communication, cross-functional work, flexibility, and facilitative leadership positively influences five dimensions of work ethic: intrinsic motivation, a sense of responsibility and trustworthiness (amanah), creativity, internalization of Islamic values (shura, ta'awun, ukhuwah), and team cohesion. This model not only improves work systems but also strengthens the mission of da’wah by positioning work as a form of worship. The implication is that da’wah institutions need to consider designing more flexible and participatory structures aligned with Islamic principles. Future research is recommended to test these conceptual findings through field studies or case studies to obtain empirical evidence